Population-based assessment of patient and provider characteristics influencing pediatric outpatient antibiotic use in a high antibiotic-prescribing state. (15th March 2020) - Katz, Sophie E.; Staub, Milner; Ouedraogo, Youssoufou; Evans, Christopher D.; Kainer, Marion A.; Griffin, Marie R.; Banerjee, Ritu
Abstract: Objective: To identify patient and provider characteristics associated with high-volume antibiotic prescribing for children in Tennessee, a state with high antibiotic utilization. Design: Cross-sectional, retrospective analysis of pediatric (aged <20 years) outpatient antibiotic prescriptions in Tennessee using the 2016 IQVIA Xponent (formerly QuintilesIMS) database. Methods: Patient and provider characteristics, including county of prescription fill, rural versus urban county classification, patient age group, provider type (nurse practitioner, physician assistant, physician, or dentist), physician specialty, and physician years of practice were analyzed. Results: Tennessee providers wrote 1, 940, 011 pediatric outpatient antibiotic prescriptions yielding an antibiotic prescribing rate of 1, 165 per 1, 000 population, 50% higher than the national pediatric antibiotic prescribing rate. Mean antibiotic prescribing rates varied greatly by county (range, 39–2, 482 prescriptions per 1, 000 population). Physicians wrote the greatest number of antibiotic prescriptions (1, 043, 030 prescriptions, 54%) of which 56% were written by general pediatricians. Pediatricians graduating from medical school prior to 2000 were significantly more likely than those graduating after 2000 to be high antibiotic prescribers. Overall, 360 providers (1.7% of the 21, 798 total providers in this dataset) were responsible for nearly 25% of both overall and broad-spectrum antibiotic prescriptions; 20% of these providers practiced in a single county. Conclusions: Fewer than 2% of providers account for 25% of pediatric antibiotic prescriptions. High antibiotic prescribing for children in Tennessee is associated with specific patient and provider characteristics that can be used to design stewardship interventions targeted to the highest prescribing providers in specific counties and specialties.